Exploring The Potential of Biodiversity: An Ethnobotany Approach As A Learning Resource At SMA Negeri 1 Tempilang - Suhartati Suhartati; Marlina Ummas Genisa; Wulandari Saputri (Universitas Wiralodra, 2024)
This study aims to analyze the ethnobotany biodiversity approach as a learning resource in the environment of SMA Negeri 1 Tempilang. Using biodiversity integrated with the community's traditional knowledge of plants (ethnobotany) in learning is crucial to increase students' understanding and awareness of the environment. The method used was a survey with a questionnaire instrument distributed to 35 SMA Negeri 1 Tempilang students to measure the level of knowledge, techniques, and obstacles to using ethnobotanical biodiversity in learning. Based on the results of the descriptive analysis, most students are at a high level of knowledge about ethnobotany, with 76 students or about 43.43% of the total population. Most of the other students were at a moderate level, with 50 students or about 28.57%. Deficient levels of knowledge have a relatively small number of students, with ten (5.71%) and 17 (9.71%), respectively. There is also a small number of students with a very high level of knowledge, namely 22 students or around 12.57%. Overall, the understanding and knowledge of ethnobotany among students is relatively good. The study results show that students understand ethnobotanical biodiversity well, but its use as a learning resource still needs improvement. The main obstacles include the limitation of learning materials and the need to utilize local potential. This study concludes the importance of integrating ethnobotany biodiversity materials in the school curriculum to increase environmental awareness and appreciation of local cultural richness. The results of this study can be a reference for the development of curriculum and learning strategies that are more relevant to local conditions.